PENELANTARAN RUMAH TANGGA SEBAGAI BENTUK KEKERASAN MENURUT UNDANG-UNDANG NO. 23 TAHUN 2004 - Anton Aulawi (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2018)
This research aims to determine: the forms of neglect of household or economic violence according to Law No. Law No. 23 Year 2004 on the Elimination of Domestic Violence, and neglect of household or economic violence become the biggest perpetrator for a woman / wife to sue her husband divorce in Serang Religious Court. This study is a combination of normative legal research and sociological / empirical legal research using a qualitative approach. Based on this research, it is found that the form of neglect of household and economic violence according to Law No. 23 of 2004 on PKDRT are: a). Not giving life b). Not providing care, and c). Economic neglect. Household neglect or economic violence becomes the biggest perpetrator for a woman / wife to sue her husband's divorce in the Religious Court Serang due to the enforcement of criminal sanctions Article 49 of Law No.23 of 2004 on PKDRT is not effective to provide protection against wife and economic violence / family dilation by husband.